Aspects of the Legal Support of Preventing Torture in the Activities of Law Enforcement Bodies - ABDIKENOV, Duman B.; BIMOLDANOV, Yerzhan M. (Journal of Advanced Research in Law and Economics, 2020)
The authors of the article have disclosed the specifics of criminal liability for committing torture in accordance with the current legislation of Kazakhstan. They have considered theoretical and legal aspects of the criminal protection of constitutional rights not to be a victim of torture, violence, other cruel or degrading treatment and punishment through the prism of international legal support for preventing torture in the activities of law enforcement bodies. The authors have defined the main criminal and criminological characteristics of the criminal offense provided for in Article 146 of the Criminal Code of Kazakhstan. Using the method of dialectical cognition and formal logical methods, the authors have taken certain steps to comprehend the phenomenon of torture, its social and legal characteristics in modern society and the law enforcement system of independent Kazakhstan. The authors have made an attempt to analyze the substantive and terminological essence of this negative phenomenon, conducted a comparative analysis of the criminal legislation of Kazakhstan and the main international laws in the field of protecting inalienable human and civil rights from torture and other cruel, inhuman or degrading treatment and punishment. In addition, this scientific article reveals some inconsistencies in the documents implemented by Kazakhstan and presents proposals for their elimination. The study results and conclusions drawn contribute to the theoretical enrichment and expansion of scientific ideas about torture as a crime, develop approaches and views forming the concept of preventing such criminal offenses and ensure the further development of scientific ideas in the field of criminal law and criminological support for preventing torture in the activities of police officers.